2021
DOI: 10.3389/fphys.2021.662978
|View full text |Cite
|
Sign up to set email alerts
|

Plant Metabolites Drive Different Responses in Caterpillars of Two Closely Related Helicoverpa Species

Abstract: The host acceptances of insects can be determined largely by detecting plant metabolites using insect taste. In the present study, we investigated the gustatory sensitivity and feeding behaviors of two closely related caterpillars, the generalist Helicoverpa armigera (Hübner) and the specialist H. assulta (Guenée), to different plant metabolites by using the single sensillum recording technique and the dual-choice assay, aiming to explore the contribution of plant metabolites to the difference of diet breadth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Among these, some secondary metabolites exert adverse effects on insects, including antifeedant, repellent, or toxic effects [ 3 , 4 ]. Common secondary metabolites with toxic effects include flavonoids and phenols, among others [ 3 , 4 , 5 ]. For example, Sun et al report that artificial diets containing gossypol, tomatine, nicotine, or capsaicin could significantly inhibit the feeding of Helicoverpa armigera larvae (Lepidoptera: Noctuidae) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, some secondary metabolites exert adverse effects on insects, including antifeedant, repellent, or toxic effects [ 3 , 4 ]. Common secondary metabolites with toxic effects include flavonoids and phenols, among others [ 3 , 4 , 5 ]. For example, Sun et al report that artificial diets containing gossypol, tomatine, nicotine, or capsaicin could significantly inhibit the feeding of Helicoverpa armigera larvae (Lepidoptera: Noctuidae) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common secondary metabolites with toxic effects include flavonoids and phenols, among others [ 3 , 4 , 5 ]. For example, Sun et al report that artificial diets containing gossypol, tomatine, nicotine, or capsaicin could significantly inhibit the feeding of Helicoverpa armigera larvae (Lepidoptera: Noctuidae) [ 5 ]. Chen et al show that feed supplemented with quercetin can directly hinder the normal growth and development of H. armigera larvae [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, sensory neurons play a very important role in state-dependent gain control of behavior [42]. A recent study showed that H. armigera and H. assulta adapted to toxic secondary metabolites at gustatory levels, which suggests the taste neurons play an important role in adaptation [43]. Our electrophysiological tests showed that the diet-induced habituation to deterrents can at least partly be explained by chemosensory desensitization of the deterrent neuron.…”
Section: Discussionmentioning
confidence: 53%
“…The feeding preference to different plants is regulated by the response of sensilla located on their mouthparts. GRNs in the two pairs of styloconic sensilla on the maxillary galea of H. armigera larvae contribute to gustatory discrimination to plant phagostimulants and deterrents (Tang et al ., 2000; Ma et al ., 2016; Wang et al ., 2017; Sun et al ., 2021). GRNs housed in the sensilla styloconica send axons directly into the taste center of GNG in H. armigera larvae (Tang et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%